2020
DOI: 10.1175/mwr-d-20-0001.1
|View full text |Cite
|
Sign up to set email alerts
|

Proactive Quality Control: Observing System Experiments Using the NCEP Global Forecast System

Abstract: Proactive Quality Control (PQC) is a fully-flow dependent QC based on Ensemble Forecast Sensitivity to Observations (EFSO). Past studies showed in several independent cases that GFS forecasts can be improved by rejecting observations identified as detrimental by EFSO. However, the impact of cycling PQC in sequential data assimilation has, so far, only been examined using the simple Lorenz ’96 model. Using a low-resolution spectral GFS model that assimilates PrepBUFR (no radiance) observations with the Local En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…We want to emphasize that EFSO estimation is not necessarily equivalent to the intrinsic quality of observation, as it depends on both the backgrounds and observations (Chen & Kalnay, 2020; Hotta et al., 2017; Lien et al., 2018). Thus, the relatively lower beneficial impact observed for moored buoys should not be interpreted as flaws in the instrument.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We want to emphasize that EFSO estimation is not necessarily equivalent to the intrinsic quality of observation, as it depends on both the backgrounds and observations (Chen & Kalnay, 2020; Hotta et al., 2017; Lien et al., 2018). Thus, the relatively lower beneficial impact observed for moored buoys should not be interpreted as flaws in the instrument.…”
Section: Resultsmentioning
confidence: 99%
“…Lien et al (2018) employed EFSO to aid data selection and guide observation use for new measurements in DA. A proactive quality control (PQC) system that removes instantaneous detrimental observations based on EFSO has been shown to be effective in enhancing the analyses and forecast quality (Chen & Kalnay, 2020;Hotta et al, 2017).…”
mentioning
confidence: 99%
“…One requires increments verification to see if these increments are right. Nonetheless, cases like this stress the need for quality control of observations, which is routinely done for conventional observations in operational DA (see e.g., Chen and Kalnay, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In ML‐based PQC, this study uses ML only for obtaining a reference state in PQC and employs the physics‐based imperfect Lorenz96 model for ensemble and extended forecasts as in model‐based PQC. Similar to Chen and Kalnay (2019); Chen and Kalnay (2020), the two PQC experiments use the forecast improved by PQC as the first guess when assimilating next observations. We performed these two PQC experiments from the analyzed ensemble from No‐PQC at t = 200, 000 for 2,000 cycles using the imperfect Lorenz96 model.…”
Section: Methodsmentioning
confidence: 99%
“…(2017) proposed proactive quality control (PQC) that denies detrimental observations diagnosed by EFSO. Previous studies demonstrated that PQC successfully improves the forecast accuracy in a low‐dimensional dynamical system and a low‐resolution operational NWP system (Chen & Kalnay, 2019, 2020; Hotta, Chen, et al., 2017). However, in general it is impossible to perform EFSO and PQC in real‐time because they require future observations.…”
Section: Introductionmentioning
confidence: 97%